2007
DOI: 10.4067/s0370-41062007000500014
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedades Diarreicas Agudas asociadas a Rotavirus

Abstract: Acute diarrhea diseases associated to Rotavirus In the period of 2001-2002, a total of 1163 fecal samples were collected from children less than five years of age with diarrhea, at the Hospital Albina Patiño and other health centers in Cochabamba city. Rotavirus infection general prevalence was 19% (220), distributed among hospitalized children 24% (77) and outpatients 17% (143). Rotavirus infections were observed along the whole study period, with highest prevalence in coldest months: April (24%), May (34%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…In 2012, the national laboratory in Colombia reported that G3 genotypes account only for 3.8% of the total genotypes isolated in the country 20 . Our results show a high proportion of G3P[8] strains (Table 3) that may suggest the potential of strain divergence, as has been previously reported in other Latin American countries 39 and in Europe 40 . Previous surveillance studies in Colombia did not identify any specific patterns in strain prevalence that support the “strain replacement hypothesis” after the introduction of the monovalent rotavirus vaccine 20 .…”
Section: Discussionsupporting
confidence: 86%
“…In 2012, the national laboratory in Colombia reported that G3 genotypes account only for 3.8% of the total genotypes isolated in the country 20 . Our results show a high proportion of G3P[8] strains (Table 3) that may suggest the potential of strain divergence, as has been previously reported in other Latin American countries 39 and in Europe 40 . Previous surveillance studies in Colombia did not identify any specific patterns in strain prevalence that support the “strain replacement hypothesis” after the introduction of the monovalent rotavirus vaccine 20 .…”
Section: Discussionsupporting
confidence: 86%
“…The literature describing the burden of rotavirus in Bolivia has demonstrated the effectiveness of rotavirus vaccine in the region. 5,6,14,16,17 Seven years before vaccine introduction at this study site, rotavirus was detected by PCR in 24% of 317 children aged < 5 years hospitalized with AGE. 17 Rotavirus prevalence was 36% when children < 2 years were analyzed separately, nearly double the prevalence described here (19%).…”
Section: Discussionmentioning
confidence: 99%
“…5,6,14,16,17 Seven years before vaccine introduction at this study site, rotavirus was detected by PCR in 24% of 317 children aged < 5 years hospitalized with AGE. 17 Rotavirus prevalence was 36% when children < 2 years were analyzed separately, nearly double the prevalence described here (19%). A study conducted at the same institution during peak rotavirus season in the year before and after vaccine introduction demonstrated a fall from 37% to 22% of rotavirus positivity in children < 12 months with AGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1989, a study by Lopez et al in Cochabamba, Bolivia, described that rotavirus was found in 22.5% of cases admitted for acute diarrhoeal disease [7]. More recently, a study conducted in 2007 also in Cochabamba, confirmed the high frequency (19%) of rotavirus in children admitted for acute diarrhoea [8]. …”
Section: Introductionmentioning
confidence: 99%